Lipidomic trajectories characterize delayed mucosal wound healing in quiescent ulcerative colitis and identify potential novel therapeutic targets - Bjerrum, Jacob Tveiten (2022)
Improving the long-term prognosis of ulcerative colitis (UC) requires sustained deep mucosal colonic healing with histologic remission, making the study of colonic tissue regeneration essential. In experimental colitis models, lipid metabolites are recognized as pivotal components of this process. This study aimed to describe the kinetics of wound healing and lipid metabolites engaged in regeneration in the normal colonic mucosa and how they are affected in UC to reveal new therapeutic targets. Experimental colonic wounds were created endoscopically in quiescent UC (n=21) and controls (n=9), and the healing process was surveilled by serial endoscopies and cross-sectional wound biopsies post-wounding. Biopsies were analyzed by liquid chromatography coupled with mass spectrometry. Endoscopic wound scores were significantly higher in UC at day two (p=0.001) and seven (p<0.0001) post-wounding, demonstrating a prolonged wound healing process. The wound scores were correlated with lipid mediators crucial for normal regeneration and sustained UC-specific changes in key phospholipids and eicosanoids, i.e., lysophosphatidylcholine, phosphatidylcholine, lysophosphatidic acid, phosphatidylglycerol, phosphatidylinositol, prostaglandin D2, and prostaglandin E1, were observed. A prolonged wound healing process is identified in quiescent UC with altered disease specific lipidomic trajectories providing potential novel therapeutic avenues for stimulating mucosal regeneration as an add-on to the traditional immune suppression treatment.